The effects of L-ascorbic acid on the mutagenicity and clastogenicity potential of holothurin - Poscidio, Glorina N. (1986)
The effects of L-ascorbic acid or vitamin C on the mutagenicity and ciastogenicity potential of holothurin were determined using Schmid's Micronucleus Tesi on ine Swiss albino miæ. Significant protection against the damaging effects of holothurin related to dosage, time and route of administration, and lolothurin source, were observed on the developing red blood cells in the bone marrow.